Domain of Quality of Life for Breast Cancer Survivors - Lilis Novitarum; Mestiana Br. Karo; Indra Hizkia (Institute of Computer Science (IOCS), 2021)
Post-treatment care and ongoing care plans for breast cancer sufferers can reduce the quality of life. Breast cancer patients who are hospitalized have negative factors, such as being away from their family and loved ones, unfamiliar hospital environment, getting diagnosis and treatment that is difficult so that the patient feels afraid of every procedure that will be given to him and makes quality his life was getting low. This study aims to identify the domains of quality of life in breast cancer sufferers. This research uses descriptive research with the sampling technique in this study using purposive sampling. The number of samples is 44 respondents in the age range 24-68 years. This research uses descriptive research using the WHO QoL BREF instrument. Based on the results of the study, it was obtained data that the physical health of breast cancer patients (79.5%) had very poor - moderate physical health categories. The psychological domain shows 66% are in good category. The domain of social relations shows 70.4% are in the medium-bad category. The Environmental Domain shows 63.6% have the environmental domain in the good-very good category. The physical health domain has the lowest score compared to other quality of life domains